Dinamika Implementasi Peraturan Daerah tentang Penyelenggaraan Menara Telekomunikasi dalam Perspektif Siyasah Tanfidziyah - Fiska Khotimah; Erina Pane; Ahmad Burhanuddin (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The implementation of telecommunication tower management in regional areas often gives rise to various issues, ranging from spatial planning irregularities and licensing problems to social and environmental impacts on the community. Normatively, the regulation of telecommunication tower management has been stipulated in various laws and regulations at both national and regional levels, emphasizing principles of spatial planning, safety, environmental aesthetics, and the protection of public interests. However, empirically, the implementation of these regional regulations still faces numerous challenges in practice. This study employs a qualitative method with a socio-legal approach, examining the gap between legal norms (das sollen) and their actual implementation in society (das sein). Data collection techniques include interviews, observation, and documentation. Data analysis is conducted by integrating the perspectives of positive law and siyasah tanfidziyah, which emphasizes the implementation of government policies in a fair, transparent, and accountable manner. The results of the study indicate that the implementation of regional regulations concerning telecommunication tower management has not been optimal. This is reflected in weak supervision by local governments, limited coordination among institutions, and low compliance of business actors with existing regulations. These conditions have led to social conflicts within the community, potential environmental degradation, and disorder in spatial planning. From the perspective of siyasah tanfidziyah, the implementation of public policy should prioritize the principles of justice (al-‘adl), public welfare (maslahah) and accountability in managing public affairs. Therefore, strengthening regulations, enhancing supervisory capacity, and fostering synergy among stakeholders are necessary to ensure that policy implementation becomes more effective and delivers optimal benefits to society.